Efecto del selenio en ratones con cáncer experimental inducido con sarcoma 180 - Hemández F., Eloísa M. (2005)
In a experimental design f longitudinal type, it was deterrmined the anticancerous effect of selenium against Sarcoma 180 inoculated to female mice of Balb C53 strain of 4 weeks age. The evaluated parameters were: tumor increasing weight (n = 20 mice), catalase activity (CAT), superoxide dismutatse activity (SOD) and survival time. The dose of seleniuro of 7.36 Ug/Kg of weightl day Was administred by oral via and it was previously assayed during 120 days in mice. The results revealed that Seleniun only increased in five days, the period of survival from the percentage of experimental animals (n=15); It did not have any effect in reducing tumor weight; the activity of CATU/ g Hb in the group of inoculated mice with sarcoma that the ones which ate a normal diet were 802.4, in the group that received Selenium was of 1017.5 but the difference was not statiscally significant; the difference between the average of SOD activity in inoculated mice with sarcoma that ate the normal diet (470 U/g Hb) and the average of inoculated mice with sarcoma that ate the supplemented diet with selenium (530 U/g Hb) was resulted stastically sarcoma 180 inducing tumorogenesis, even when it does not have a significant effect in exted survival perido of experimental animals.